2021
DOI: 10.3389/fimmu.2021.635097
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Antibodies Against the Crude Capsular Extract in the Immune Response of Porcine Alveolar Macrophages to In Vitro Infection of Various Serovars of Glaesserella (Haemophilus) parasuis

Abstract: In Glässer’s disease outbreaks, Glaesserella (Haemophilus) parasuis has to overcome the non-specific immune system in the lower respiratory tract, the alveolar macrophages. Here we showed that porcine alveolar macrophages (PAMs) were able to recognize and phagocyte G. parasuis with strain-to-strain variability despite the presence of the capsule in virulent (serovar 1, 5, 12) as well in avirulent strains (serovar 6 and 9). The capsule, outer membrane proteins, virulence-associated autotransporters, cytolethal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Correspondingly, a moderated macrophage response in the lung tissue of immunized piglets likely reflected a more balanced and effective immune strategy. This reduction in the need for extensive inflammatory infiltration, coupled with minimized collateral tissue damage, was facilitated by the G. parasuis opsonization by post-vaccinal immunoglobulins, leading to effective phagocytosis by alveolar macrophages (28). This scenario underscores the efficacy of the vaccine not only in preventing severe disease and mortality, but also in modulating the immune response to minimize collateral tissue damage, thus offering a comprehensive protective mechanism against G. parasuis infection.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, a moderated macrophage response in the lung tissue of immunized piglets likely reflected a more balanced and effective immune strategy. This reduction in the need for extensive inflammatory infiltration, coupled with minimized collateral tissue damage, was facilitated by the G. parasuis opsonization by post-vaccinal immunoglobulins, leading to effective phagocytosis by alveolar macrophages (28). This scenario underscores the efficacy of the vaccine not only in preventing severe disease and mortality, but also in modulating the immune response to minimize collateral tissue damage, thus offering a comprehensive protective mechanism against G. parasuis infection.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, for virulent H. parasuis , escape is the first step in inducing Glässer disease. Previous studies have shown that antibody-mediated opsonization can facilitate the phagocytosis of virulent H. parasuis by PAMs, which prevents the development of the disease in the early stages of infection ( Matiaskova et al., 2021 ). In the present study, we found that there were six linear B-cell epitopes in the loop region of OmpP2 that were exposed to the surface of bacteria, distributed in loop2 (Pt5, Pt5-II), loop3 (Pt7/Pt7a, Pt9), loop4 (Pt11/Pt11a), loop5 (Pt14), and loop8 (Pt21), suggesting that these epitopes and corresponding antibodies may participate in the opsonization and phagocytosis resistant of H. parasuis .…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria-derived antimicrobial effectors like mROS primarily generated during mitochondrial metabolism aid in bacterial killing [34]. When G. parasuis infected, released ROS gathered at the bacterial site to resist the bacteria [35]. However, the aggregation of mitochondria oxidative catastrophe induces cell death and inflammation [36].…”
Section: Discussionmentioning
confidence: 99%
“…When G . parasuis infected, released ROS gathered at the bacterial site to resist the bacteria [ 35 ]. However, the aggregation of mitochondria oxidative catastrophe induces cell death and inflammation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%